Emerging organic contaminants in groundwater under a rapidly developing city (Patna) in northern India dominated by high concentrations of lifestyle chemicals. (1st January 2021) - Richards, Laura A.; Kumari, Rupa; White, Debbie; Parashar, Neha; Kumar, Arun; Ghosh, Ashok; Kumar, Sumant; Chakravorty, Biswajit; Lu, Chuanhe; Civil, Wayne; Lapworth, Dan J.; Krause, Stefan; et al.
Abstract: Aquatic pollution from emerging organic contaminants (EOCs) is of key environmental importance in India and globally, particularly due to concerns of antimicrobial resistance, ecotoxicity and drinking water supply vulnerability. Here, using a broad screening approach, we characterize the composition and distribution of EOCs in groundwater in the Gangetic Plain around Patna (Bihar), as an exemplar of a rapidly developing urban area in northern India. A total of 73 EOCs were detected in 51 samples, typically at ng.L −1 to low μg.L −1 concentrations, relating to medical and veterinary, agrochemical, industrial and lifestyle usage. Concentrations were often dominated by the lifestyle chemical and artificial sweetener sucralose. Seventeen identified EOCs are flagged as priority compounds by the European Commission, World Health Organisation and/or World Organisation for Animal Health: namely, herbicides diuron and atrazine; insecticides imidacloprid, thiamethoxam, clothianidin and acetamiprid; the surfactant perfluorooctane sulfonate (and related perfluorobutane sulfonate, perfluorohexane sulfonate, perfluorooctanoic acid and perfluoropentane sulfonate); and medical/veterinary compounds sulfamethoxazole, sulfanilamide, dapson, sulfathiazole, sulfamethazine and diclofenac. The spatial distribution of EOCs varies widely, with concentrations declining with depth, consistent with a strong dominant vertical flow control. Groundwater EOC concentrations in Patna were found to peak within ∼10 km distance from the River Ganges, indicating mainly urban inputs with some local pollution hotspots. A heterogeneous relationship between EOCs and population density likely reflects confounding factors including varying input types and controls ( e.g. spatial, temporal), wastewater treatment infrastructure and groundwater abstraction. Strong seasonal agreement in EOC concentrations was observed. Co-existence of limited transformation products with associated parent compounds indicate active microbial degradation processes. This study characterizes key controls on the distribution of groundwater EOCs across the urban to rural transition near Patna, as a rapidly developing Indian city, and contributes to the wider understanding of the vulnerability of shallow groundwater to surface-derived contamination in similar environments. Graphical abstract: Image 1 Highlights: Emerging organic contaminants are widely detected in groundwater used for drinking. Lifestyle compounds such as sucralose dominate EOC concentrations in most samples. Depth controls are more important than river proximity, population or season. Urban EOCs are linked to wastewater, pharmaceuticals, agrochemicals and industry. Seventeen compounds are identified as priority substances for monitoring. Abstract : Emerging Organic Contaminants in groundwater under a rapidly developing city (Patna) in Northern India are dominated by relatively high concentrations of lifestyle chemicals and a relatively high number of medical/veterinary compounds and agrochemicals.